2012
DOI: 10.1136/jmedgenet-2012-100737
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies mutations inLZTFL1, a BBSome and smoothened trafficking regulator, in a family with Bardet–Biedl syndrome with situs inversus and insertional polydactyly

Abstract: LZTFL1, encoding the human leucine zipper transcription factor like 1, has been recently shown to be an important negative regulator of BBSome ciliary trafficking and Shh signalling. This study shows that absence of LZTFL1 leads to a BBS phenotype with enhanced developmental abnormalities associated with cellular Shh dysfunction. LZTFL1 is a novel BBS gene (BBS17).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 22 publications
3
101
0
4
Order By: Relevance
“…LZTFL1 mutations were then found in human patients with BBS, rendering it the 17th BBS gene (BBS17) (24,25). More recently, it was shown that Lztfl1 cycles between cilia and the cytoplasm and facilitates removal of the BBSome from cilia (26).…”
Section: Significancementioning
confidence: 99%
“…LZTFL1 mutations were then found in human patients with BBS, rendering it the 17th BBS gene (BBS17) (24,25). More recently, it was shown that Lztfl1 cycles between cilia and the cytoplasm and facilitates removal of the BBSome from cilia (26).…”
Section: Significancementioning
confidence: 99%
“…BBS is a genetically heterogeneous condition for which 19 BBS14/CEP290, BBS15/WDPCP/FRITZ, BBS16/SDCCAG8, BBS17/LZTFL1, BBS18/BBIP10/BBIP1 and BBS19/IFT27; ( [9][10][11][12][13][14] and references within). This heterogeneity was originally thought to be the cause of the significant inter-familial variability that characterizes the syndrome.…”
Section: The Genetics Of Bbsmentioning
confidence: 99%
“…140 Many BBS proteins have been shown to localize to the photoreceptors, [140][141][142][143] and loss of most of the BBSome proteins leads to retinal degeneration in model organisms and humans as part of the multi-organ condition Bardet-Biedl syndrome (BBS). 141,[144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159] For example, Bbs1 knock-in mutant mice develop disorganized OS, and exhibit degeneration of IS and OS. 160 Other work has exemplified the disease mechanism of disrupted trafficking that underlies the retinal degeneration in this ciliopathy.…”
mentioning
confidence: 99%